2018
DOI: 10.4314/mmj.v30i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use of seclusion in an inpatient psychiatric unit in Lilongwe, Malawi

Abstract: BackgroundData on the use of seclusion for psychiatric inpatients in sub-Saharan Africa are extremely limited. Though seclusion is sometimes necessary for patients that pose a threat to themselves or others, adverse physical and psychological sequelae from the experience are increasingly being recognized, leading to efforts to reduce its use. The purpose of this study was to calculate the frequency of seclusion in patients hospitalized in an inpatient psychiatric unit in Lilongwe, Malawi, and to identify facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Individual and institutional variations in the preferences of the methods used to measure, document and/or report restrictive care practice incidents across different geographical regions (Pérez‐Revuelta et al., 2021) or healthcare services could also explain some of these variations (El‐Abidi et al., 2021). This illustrates a need to understand the changing nature of mental health services and adapt similar documentation (Barnett, 2018) and reporting cultures to enhance ongoing monitoring and evaluation of restrictive care practice reduction strategies (McKeown et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Individual and institutional variations in the preferences of the methods used to measure, document and/or report restrictive care practice incidents across different geographical regions (Pérez‐Revuelta et al., 2021) or healthcare services could also explain some of these variations (El‐Abidi et al., 2021). This illustrates a need to understand the changing nature of mental health services and adapt similar documentation (Barnett, 2018) and reporting cultures to enhance ongoing monitoring and evaluation of restrictive care practice reduction strategies (McKeown et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of seclusion was also found to decrease with time since admission in that study, which was not noted in our study. A retrospective study of psychiatric inpatients in Malawi found that male patients had increased odds of being secluded 36. In that study, no association was found between seclusion and age; diagnosis of alcohol use disorder, marijuana use disorder or schizophrenia; involuntary admission; presence of hallucinations; suicidality; or commission of violent acts before admission.…”
Section: Discussionmentioning
confidence: 99%
“…These providers have training in acute management and mitigation techniques that are targeted to address agitation secondary to psychiatric disturbances. A variety of techniques, agitation scoring systems, and clinical triaging tools are present and discussed in the psychiatric literature which allows providers to assess developing and established situations [4,18,19,21,[28][29][30]. These providers can provide additional support and techniques to properly engage with Contemporary Topics in Patient Safety -Volume 2 the patient, better assess the source of their agitation, and provide recommendations on further therapy or medication.…”
Section: Contemporary Topics In Patient Safety -Volumementioning
confidence: 99%